Women's Voice and Agency in the MGNREGA in Odisha: Baseline Data - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
This dataset contains baseline information for the project "Women's Voice and Agency in the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) in Odisha," conducted in April-May 2023 across five districts in the eastern coastal state of Odisha, India. The study aimed to evaluate interventions designed to enhance women’s voice and agency in selecting assets to be created under the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), a national workfare program. The baseline data focused on female respondents actively participating in MGNREGA, capturing their demographic and socioeconomic profiles, experiences, and knowledge of the program, as well as their perspectives on agency and voice. Additional interviews were conducted with Gram Rozgar Sewaks, the primary program functionaries, and community representatives familiar with village-level facilities. The sample included 50 Gram Panchayats (villages) from each of the five districts, targeting 15 female respondents per Gram Panchayat, for a total of 3,750 intended respondents. However, due to community refusals in one district, interviews could not be conducted in 30 of the 50 Gram Panchayats, resulting in a final sample size of approximately 3,426 female respondents, 220 Gram Rozgar Sewaks, and 229 community-level interviews.